THE ROLE OF WRESTLERS INDIVIDUAL PSYCHOLOGICAL CHARACTERISTIC IN COMPETITIVE ACTIVITY - Poghosyan, Ira (Modern Psychology, 2025)
The article examines the role of individual psychological characteristics of wrestlers in their competitive performance. The study involved 45 Greco-Roman and freestyle wrestlers (aged 18-32), divided into three groups based on their qualification level. Using standardized psychological assessment tools, the research revealed significant differences in emotional stability, self-control, anxiety, aggression management, and motivational orientation between highly qualified and novice wrestlers.    The results showed that highly qualified wrestlers demonstrate higher levels of emotional stability, courage, and self-control, along with lower levels of anxiety and tension. They predominantly display instrumental aggression as a means of gaining competitive advantage, while beginners show more reactive aggression. The ratio of achievement motivation to failure avoidance motivation also differs significantly between qualification groups.    Correlation analysis confirmed significant relationships between psychological characteristics and competitive performance indicators. The findings can be used to develop individualized psychological preparation programs for wrestlers, taking into account their personal characteristics, with special attention to emotional stability, self-control, aggression management, and optimization of motivational orientation.
Keywords: psychological factors; emotions; mental processes; competitive; wrestler; mental reliability; emotional state; personal factors